2015
DOI: 10.1007/s40520-014-0297-9
|View full text |Cite
|
Sign up to set email alerts
|

Delirium symptoms during hospitalization predict long-term mortality in patients with severe pneumonia

Abstract: Delirium symptoms are independent predictors of one-year mortality in hospitalized patients with severe pneumonia. Further studies should confirm our results using prospective methods of collecting data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
2
12
4
1
Order By: Relevance
“…Although delirium has frequently been associated with mortality in geriatric and other critical care samples, 23 our is the first to demonstrate an association between delirium and subsequent mortality. Of note, although previous studies have generally suggested that delirium is associated with worse 6-month 24 and 12-month mortality, 25 our findings suggest that the association between NSE (which was primarily delirium) and posttransplant mortality increased over time, rising to its greatest magnitude approximately 2 years postoperatively. Although the reasons behind the timing of this association are unclear, it is possible that impaired cognition, which is one of the primary long-term effects of severe delirium, leading to nonadherence with medical regimen or to more debilitated state, could explain this association.…”
Section: Discussioncontrasting
confidence: 59%
“…Although delirium has frequently been associated with mortality in geriatric and other critical care samples, 23 our is the first to demonstrate an association between delirium and subsequent mortality. Of note, although previous studies have generally suggested that delirium is associated with worse 6-month 24 and 12-month mortality, 25 our findings suggest that the association between NSE (which was primarily delirium) and posttransplant mortality increased over time, rising to its greatest magnitude approximately 2 years postoperatively. Although the reasons behind the timing of this association are unclear, it is possible that impaired cognition, which is one of the primary long-term effects of severe delirium, leading to nonadherence with medical regimen or to more debilitated state, could explain this association.…”
Section: Discussioncontrasting
confidence: 59%
“…Unlike other studies [38,39], there was no significant difference in mechanical ventilation time between delirium and non-delirium patients of pulmonary diseases. The most probable answer for this might be that the patients with pulmonary diseases which our studied included were patients with respiratory failure were ineffective in medical treatment, and the other reason could take for considered is the fact that we had a rather small number of patients with delirium who were documented and analyzed.…”
Section: Discussioncontrasting
confidence: 92%
“…( 11 , 13 , 22 , 23 ) In fact, an association between age and delirium has often been described, thereby establishing delirium as a frequent complication in older ICU patients. ( 2 , 11 , 13 , 24 - 26 ) An independent association between delirium and long-term mortality has been detected in critically ill patients and in those with severe pneumonia, ( 25 , 27 - 29 ) but a counterfactual analysis showed that delirium prolongs the ICU stay but does not cause death in critically ill patients. ( 9 ) Thus, the relationship between delirium and mortality remains unclear.…”
Section: Discussionmentioning
confidence: 99%